Surgical risk assessment in Hiv-infected patients treated within the penitentiary system of Kemerovo region - A. A. Malashenko; K. A. Krasnov; O. A. Krasnov (Фундаментальная и клиническая медицина, 2021)
Aim. To assess the surgical risk in HIV-infected patients who received the surgical treatment within the penitentiary system of Kemerovo Region.Materials and Methods. We retrospectively analysed the physical status and the extent of surgical risk in 296 HIV-infected patients who underwent elective (n = 201) or emergency (n = 95) surgery in Hospital №1 (Kemerovo) from 2015 to 2018. Physical status was assessed according to American Society of Anesthesiologists (ASA) Physical Status Classification System. Surgical risk was scored according to Moscow Scientific Society of Anesthesiologists and Critical Care.Results. The majority of patients had 3 (48.4 and 36.3% in emergency and elective patients, respectively) or 4a (30.5 and 45.8% in emergency and elective patients, respectively) stages of HIV infection. Opportunistic infections were diagnosed in 49.3% of patients and were always accompanied by superficial mycoses. Physical status of most patients (47.4% and 63.7% in emergency and elective patients, respectively) corresponded to ASA physical status class 3. Emergency patients mainly had surgical risk class 3 (n = 50, 52.6%) while elective patients often had surgical risk class 2 (n = 106, 52.7%). The prevalence of postoperative complications, most often impaired wound healing, was 9.8%.Conclusion. More than 80% of HIV-infected patients who underwent surgical interventions within the penitentiary system of Kuzbass were at III or IV stages of HIV infection, entailing a high frequency of opportunistic diseases such as superficial mycoses and dictating the need to include antifungal treatment into the surgical treatment. Impaired wound healing was the most frequent postoperative complication.